Pengaruh Logoterapi Terhadap Hipertensi Pada Pasien Lanjut Usia - Fatimah, Agnes (Jurnal Kedokteran Indonesia, 2009)
Background: Behavior cognitive and relaxation types of psychotherapy have been proven effectivefor treatment of patients with somatic disturbance. However, research into the benefit of logotherapy(LGT) is lacking. Acceptance of conditions gives better meaning of life and psychological approachhelps enhance the patientâs coping ability. Coping ability creates balance in the nervous systemregulation, HPA axis, innate component, and adaptive immunity system. It in turn will bring about thechange in the patientâs blood pressure. This study is aimed to determine the effectiveness oflogotherapy on reducing hypertension among elderly patients.Methods: This study used pre and posttest with control group quasi experimental design, conductedfrom July to October 2008. The study subjects were purposively sampled from members of PWRI(Association of the Elderly of the Republic of Indonesia) in Urutsewu-Ampel Boyolali, Central Java,who met criteria for inclusion. Riester quicksilver sphygmomanometer and Riester stethoscope wereused for measuring blood pressure. T-test was used to test the mean difference in the reduction ofblood pressure. The analysis was run by SPSS version 15.0 program.Results: There was statistically significant difference in the reduction of systolic blood pressure (p<0.001)and diastolic blood pressure (p=0.019), between the logotherapy group and the control group.Conclusion: Logotherapy administered in conjuction with anti-hypertensive drug reduces systolicblood pressure and diastolic pressure in elderly patients with hypertension. Logotherapy can be usedas an additional therapy for patients with hypertension.Keywords: logotherapy, hypertension, elderly